Relationships between neurocognitive functioning, mood, and quality of life in patients with temporal lobe glioma - Noll, Kyle R. (Psychooncology, 2015)
OBJECTIVE: While neurocognitive functioning (NCF) and mood disturbance share a relationship with health-related quality of life (HRQOL), few studies have examined relationships between these constructs in glioma patients prior to treatment. METHODS: Newly diagnosed patients with glioma in the left (N=73; 49% glioblastoma) or right (N=30; 57% glioblastoma) temporal lobe completed neuropsychological testing and self-report measures of HRQOL (Functional Assessment of Cancer Treatment-General and Brain module) and mood (Beck Depression Inventory-Second Edition and State-Trait Anxiety Inventory). RESULTS: Verbal learning and memory, executive function, and language abilities were associated with various HRQOL scales. Stepwise linear regression showed that verbal learning predicted scores on the General Well-being scale and Brain module, processing speed predicted Social Well-being scores, and executive functioning predicted Functional Well-being scores on the FACT. Upper extremity strength also predicted scores on the Functional Well-being subscale and Brain module. Mood was more strongly associated with HRQOL domains than NCF, with depressive symptoms accounting for a large proportion of variance across most subscales. CONCLUSIONS: In patients with temporal lobe glioma, depressive symptoms are strongly related to most aspects of HRQOL but not with NCF. NCF, specifically verbal learning and memory, executive functioning, and processing speed, also show direct relationships with numerous aspects of HRQOL. These findings underscore the importance of multimodal assessment of NCF and mood in this population.